Analytical Hierarchy Process (AHP) untuk Zona Kerentanan Tanah Longsor di Daerah Gumelar - Reza Fahmi Pahlevi; Dimara Kusuma Hakim; Tito Pinandita; Muhammad Hamka (Politeknik Piksi Ganesha Indonesia, 2025)
Landslides are geological disasters that frequently occur in areas with steep topography and minimal vegetation, including in Gumelar Subdistrict, Banyumas Regency. This study aims to map landslide vulnerability zones using a multi-criteria approach with the Analytical Hierarchy Process (AHP) method integrated into a Geographic Information System (GIS). Four main parameters analyzed include slope gradient, rainfall, lithology, and land cover, with weights determined through a pairwise comparison matrix by experts. The results indicate that slope gradient (49.2%) and rainfall (30.9%) are the dominant factors in determining vulnerability levels. The resulting vulnerability map shows the distribution of areas with low, moderate, and high risks, validated using field landslide event data. This study provides an accurate spatial basis for landslide disaster mitigation planning in the study area